2014
DOI: 10.1177/0004563214551613
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of insulin analogues with three insulin assays

Abstract: In the Elecsys(®) E170 assay, relevant cross-reactivity was only detected with insulin glargine, whereas in the other analysers all analogues except glulisine showed significant interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 18 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…Low blood glucose levels combined with high insulin and low C-peptide prompted the physician to consider the diagnosis of autoimmune hypoglycemia, and order a specific test to confirm the diagnosis using special assay. It has been reported that in the insulin analyzer used in our hospital, Immulite® 2000 (Siemens Healthcare Diagnostics), all insulin analogues including insulins lispro, aspart, glargine, detemir, probably except for glulisine, showed significant interference and caused detectable insulin levels in type 1 patients receiving the insulin analogue treatments [10].…”
Section: Discussionmentioning
confidence: 98%
“…Low blood glucose levels combined with high insulin and low C-peptide prompted the physician to consider the diagnosis of autoimmune hypoglycemia, and order a specific test to confirm the diagnosis using special assay. It has been reported that in the insulin analyzer used in our hospital, Immulite® 2000 (Siemens Healthcare Diagnostics), all insulin analogues including insulins lispro, aspart, glargine, detemir, probably except for glulisine, showed significant interference and caused detectable insulin levels in type 1 patients receiving the insulin analogue treatments [10].…”
Section: Discussionmentioning
confidence: 98%
“…As one of the antibodies in the Roche immunoassay is directed against the carboxy-terminal region of the B chain, it does not detect insulin aspart, lispro, detemir or gluisine. 2,6 Although insulin glargine also has a modification at the carboxy-terminal end of the B chain, it undergoes biotransformation in human serum to metabolites M1 and M2 and the M1 metabolite binds to the Roche assay. 6,7 In contrast, the antibodies in the Advia Centaur immunoassay are directed against a different region of the insulin molecule.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Although insulin glargine also has a modification at the carboxy-terminal end of the B chain, it undergoes biotransformation in human serum to metabolites M1 and M2 and the M1 metabolite binds to the Roche assay. 6,7 In contrast, the antibodies in the Advia Centaur immunoassay are directed against a different region of the insulin molecule. Therefore, it recognises insulin aspart, lispro, detemir and glargine, but not glulisine, because of the additional amino acid substitution at the amino-terminal end of the B chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five insulin analogues listed in the study of Dayaldasani et al 1 are also structurally different from naturally secreted human insulin. They are engineered recombinant forms in which amino acids in specific locations have been altered.…”
Section: Insulin Analogues As a New Example Of Interference In Insulimentioning
confidence: 99%